WASIAT TERHADAP HARTA PENINGGALAN UNTUK ANAK ANGKAT DIPANDANG DARI HUKUM ISLAM - Ade Kurniawan Akbar (AL IMARAH : JURNAL PEMERINTAHAN DAN POLITIK ISLAM, 2018)
Abstract: Islamic jurists suggest that a will is ownership based on a person who declares a will died in the way of goodness without demanding compensation or tabarru '. In Islamic law, adopted children are not heirs, so if the adoptive parents die, the adopted child does not get a heritage. However, of course this is not fair for adopted children who are like their own children by their adoptive parents. For this reason, a will for the adopted child is needed to obtain the inheritance of the adoptive parents. The purpose of this study, namely: 1). To study and explain the provisions of Islamic law regarding testaments to inheritance. 2). To study and explain the provisions of Islamic law regarding testaments to inheritance for adopted children. This type of research belongs to the category of normative legal research. Conclusion, Many inheritance that can be inherited for adopted children is as much as 1/3 of all assets left behind, where the assets are in the distribution system that before the distribution of inheritance to the heirs is carried out, the obligatory will must be fulfilled first. In the division of obligatory wills, which have been determined according to Islamic law, what must be considered is that the part of the adopted child is a third part and must not exceed the minimum portion received by the heirs.Keywords: testament, adoption, inheritance